Outcome of patients with acute kidney injury in severe sepsis and septic shock treated with early goal-directed therapy in an intensive care unit - Rahmani, Rifat; Memon, Javed I.; Ahmad, Wasim; al-Juhayman, Abd al-Majid (Saudi journal of kidney diseases and transplantation, 2014)
Acute kidney injury (AKI) in the intensive care unit (ICU) is commonly caused by severe sepsis and septic shock. There is limited data regarding the incidence and outcomes of patients developing AKI treated with early goal-directed therapy (EGDT). Our aim was to observe the incidence and outcomes of patients with AKI in severe sepsis and septic shock, treated with EGDT as compared with historic controls. Study subjects included all adults admitted to the ICU with a diagnosis of severe sepsis and septic shock prior to (historic controls) and after introduction of EGDT (intervention group). Two groups were compared for incidence of AKI, length of ICU and hospital stay, incidence and requirement for renal replacement therapy, serum creatinine at discharge, maximum RIFLE (Risk, injury, failure, loss, end stage) in each group and 28-day mortality. Two groups were well matched for age, sex, (April 16, 2014) and acute physiological and chronic health evaluation (APACHE) II scores. We found no significant difference in the incidence of AKI (51 % vs. 46 %). There was no statistical difference in any of the above outcomes, including 28-day mortality in historic controls versus patients treated with EGDT. Septic AKI is a complex syndrome. The incidence and outcomes have not improved despite advances in sepsis management and EGDT. Very early detection of septic AKI and targeted therapies may improve outcomes.